2004
DOI: 10.1080/00365510410002913
|View full text |Cite
|
Sign up to set email alerts
|

ProBNP‐derived peptides in cardiac disease

Abstract: The natriuretic peptides constitute a family of structurally related peptides that regulate fluid homeostasis, vascular tonus and growth. After the discovery of an endocrine component of the heart almost 25 years ago, the cardiac natriuretic peptides have now been fully accepted as useful markers in diverse aspects of cardiology including as diagnostic, therapeutic and prognostic markers of cardiac disease. In humans, atrial natriuretic peptide (ANP) and B-type natriuretic peptide (BNP) are mainly synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…In healthy individuals, the main site of BNP gene expression is the atria, but in disease states, ventricular gene expression is up-regulated [20,21]. Ventricular wall stress stimulates synthesis and release of both atrial and brain natriuretic peptides, concentrations of which increase in heart failure [5,19]. Changes in wall stress may explain our differences in levels of natriuretic peptides during the treatment protocol in our study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In healthy individuals, the main site of BNP gene expression is the atria, but in disease states, ventricular gene expression is up-regulated [20,21]. Ventricular wall stress stimulates synthesis and release of both atrial and brain natriuretic peptides, concentrations of which increase in heart failure [5,19]. Changes in wall stress may explain our differences in levels of natriuretic peptides during the treatment protocol in our study.…”
Section: Discussionmentioning
confidence: 71%
“…The natriuretic peptide system plays an important role in the regulation of diuresis and natriuresis, blood pressure and cardiomyocyte growth. This system functions to retard the progression of heart failure, the opposite of the effect of neurohumoral systems such as the renin-angiotensinaldosterone and the sympathetic nervous system [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that many B-type-related peptides circulate in human blood (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In particular, large amounts of pro-hormone peptide (i.e., proBNP) can be detected in plasma of patients with HF (15-22, 25, 32).…”
Section: Introductionmentioning
confidence: 99%
“…They have an important role in regulation of fluid homeostasis, blood pressure/vascular tone, and cardiomyocyte growth. This system functions to retard the progression of heart failure, opposite to the effect of neurohumoral systems like the renin-angiotensin-aldosterone system and the sympathetic nervous system [1, 2]. …”
Section: Introductionmentioning
confidence: 99%